(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study is intended to determine the effect of product design and service quality on consumer purchasing decisions at Batik Manonjaya Tasikmalaya. The research method used is a quantitative method and is included in descriptive verification research. The sampling technique used in this study is non-probability sampling with the incidental sampling technique with a total sample size of 110 people. While the method of analysis used in this study is multiple linear regression analysis at a significance level of 5%. The program used in analyzing data used the Statistical Package for Social Sciences (SPSS) Ver. 25. The results of this study indicate that the questionnaire is valid and reliable. The results of hypothesis testing in this study are Ha: β1 ≠ 0 if ρ - value <0.05, which means that Ho is rejected and Ha is accepted. The results also show that the product design variable has a partial effect on the purchasing decision variable with a significant level of consideration of 0.002 <0.05. And the results also show that the service quality variable has a partial effect on the purchasing decision variable with a significant level of consideration of 0.000 <0.05. The value of F count 54.404 is greater than F table 3.08, so the variable product design and service quality simultaneously affect the purchasing decision with a coefficient of determination of 50.4%.